HOW EASY TO MAKE AN ONLINE EVALUATION - Akbar Nasrum (USN Kolaka, 2022)
The purpose of this study is to explain the procedure for making online questions using the jeruq.com website and describe the advantages and disadvantages of the question maker website. This research is a qualitative descriptive study. The instruments used in collecting data were exam questions made using the jeruq.com website, interview guidelines, and most importantly the researchers themselves. Based on the results of trials and interviews conducted, several results were obtained including: (1) The fraud detector in the system has not functioned optimally, especially if the exam uses a smartphone. (2) In order for the conclusions in the item analysis to be more precise, the number of answer items in each item must be the same as the number in the system. The final conclusion obtained is that this website is very helpful for teachers or lecturers who want to make online exam questions quickly.